Governing disorder : UN peace operations, international security, and democratization in the post-Cold War era - Zanotti, Laura (Pennsylvania State University Press, 2011)
"Examines post-Cold War discourses about the use of power to promote international security. Uses case studies of United Nations interventions in Haiti and Croatia to highlight the dynamics at play in encounters between local societies and international peacekeepers"--Provided by publisher.